Analisis Kinerja Keuangan Perusahaan Menggunakan Metode EVA, MVA dan FVA - Zaki, Amry; Challen, Auliffi Ermian (Jurnal Audit dan Perpajakan (JAP), 2022)
The purpose of this study was to determine the financial performance of companies in the food and beverages sub-sector. using economic value-added, market value, and financial value-added methods. The population of this study is manufacturing companies listed on the  Indonesia stock exchange. The total sample used 9 companies in the food and beverages sub-sector. The data analysis of this study used the calculation of EVA, MVA, and FVA methods. The result showed the 7 companies produced positive values in the 2016-2020 Period. Companies with positive value succeeded in creating economic added value for the company and shareholders. The result of the MVA Calculation shows the 6 companies produce a positive MVA value which indicates that the company has succeeded and increased the added value of the invested capital. While the result of the FVA calculation, there are 8 companies that have succeeded in producing positive FVA Value,  this shows that the companies are able to create financial added.